2011
DOI: 10.1182/blood-2011-05-355354
|View full text |Cite
|
Sign up to set email alerts
|

Factor VIII alters tubular organization and functional properties of von Willebrand factor stored in Weibel-Palade bodies

Abstract: In endothelial cells, von Willebrand factor (VWF) multimers are packaged into tubules that direct biogenesis of elongated Weibel-Palade bodies (WPBs). WPB release results in unfurling of VWF tubules and assembly into strings that serve to recruit platelets. By confocal microscopy, we have previously observed a rounded morphology of WPBs in blood outgrowth endothelial cells transduced to express factor VIII (FVIII). Using correlative lightelectron microscopy and tomography, we now demonstrate that FVIII-contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 50 publications
(81 reference statements)
2
22
0
Order By: Relevance
“…This suggests that round WPBs are equally well released when compared to elongated WPB. This is in line with previous observations that WPBs containing FVIII, leading to the formation of spherical WPBs, can still release their cargo (Van den Biggelaar et al, 2009;Bouwens et al, 2011). Spherical WPBs in canine endothelial cells bearing the p.Tyr87Ser mutation, are rapidly releasing their cargo upon stimulation with appropriate secretagogues (Haberichter et al, 2005).…”
Section: Discussionsupporting
confidence: 79%
“…This suggests that round WPBs are equally well released when compared to elongated WPB. This is in line with previous observations that WPBs containing FVIII, leading to the formation of spherical WPBs, can still release their cargo (Van den Biggelaar et al, 2009;Bouwens et al, 2011). Spherical WPBs in canine endothelial cells bearing the p.Tyr87Ser mutation, are rapidly releasing their cargo upon stimulation with appropriate secretagogues (Haberichter et al, 2005).…”
Section: Discussionsupporting
confidence: 79%
“…TEM samples were processed as described. 23 Correlated fluorescence and electron micrographs were overlaid in Adobe Photoshop CS6 (Adobe Inc, San Jose, CA) using the nuclei in the area of interest to align the two images. For electron tomography, 10-nm gold fiducials were added to the samples.…”
Section: Correlative Light and Electron Microscopymentioning
confidence: 99%
“…Immunofluorescence microscopy showed that VWF was stored by BOECs in elongated organelles ( Figure 1B) that displayed internal striations under electron microscopy (data not shown). 25 Furthermore, these organelles also stored the WPB-specific membrane protein P-selectin ( Figure 1B). These data indicate that VWF was stored in authentic WPB.…”
Section: Isolation and Characteristics Of Boecsmentioning
confidence: 99%
“…24 It has been suggested that BOECs provide a useful system to study the release of WPB and the formation of VWF strings. 25 In addition, morphology of WPB in the BOECs derived from a single patient with VWD has been characterized in a recent study. 17 The aim of the current study was to further explore the feasibility of using BOECs as an endothelial cell model to study the pathogenic nature of VWF mutations at the molecular cellular level.…”
Section: Introductionmentioning
confidence: 99%